Accounting for Financial Instruments in an Uncertain World: Controversies in IFRS in the Aftermath of the 2008 Financial Crisis - Richard Pucci (Copenhagen Business School (CBS), 2017)
This thesis explores the response of the International Accounting Standards Board (IASB) to the 2008 financial crisis. At the onset of the crisis, the international accounting standard on financial instruments, IAS 39, was blamed for exacerbating the ill effects of the economic downturn and significant changes were called for by numerous actors including the G20 and the Financial Stability Forum. The dissertation focuses on the events surrounding the emergency amendments to the standard in October 2008 along with the IASB's long-term response to the crisis, IFRS 9. Moreover, the project analyzes the IFRS 9 endorsement process in the European Union. Attention is directed towards broadening our awareness of the interplay among diverse actors in the revision of international accounting standards. Ultimately, it is hoped that the thesis will broaden extant understandings of the manner in which accounting standard-setters cope with multiple and conflicting interests which crystallize in times of crisis. The project contributes to the literature on accounting standard-setting by further explicating three pertinent issues; namely, (1) how agreements are reached in the critical moments of standard-setting, (2) the influence of economics on accounting standards, and (3) how financial accounting texts are solidified. The thesis is comprised of three papers.
hdl:10398/9477
Keywords: 650